Improved Composite Q-Function Approximation and its Application in ASEP of Digital Modulations over Fading Channels - Markovic, Aleksandar; Peric, Zoran; Panic, Stefan; Spalevic, Petar; Todorovic, Zoran (Elektronika ir Elektrotechnika, 2017)
In this paper, capitalizing on Mils ratio for Q-function approximation, we have presented novel improved composite Q-function approximation. Based on our improved approximation, we have further presented tight approximation for the average symbol error probability (ASEP) expressions of digital modulations over Nakagami-m fading channels. First, comparison to other known Q-function closed-form approximations has been performed, and it has been shown that accuracy improvement has been achieved in the observed range of values. Further, it has been shown that by using proposed approximation, values of average symbol error probability (ASEP) for some applied modulation formats could be efficiently and accurately evaluated when transmission over Nakagami-m fading channels is observed. Also, it has been shown in the paper that by using proposed approximation, observed ASEP measures are bounded more closely, than by using other known Q-function closed-form approximations. DOI: http://dx.doi.org/10.5755/j01.eie.23.3.18338